Biometrics and the disciplining of democracy: technology, electoral politics, and liberal interventionism in Chad. Issue 8 (17th November 2021) - Debos, Marielle
ABSTRACT : In a large number of countries in Africa, biometric identification technologies have become a key element of voter registration procedures. Based on an in-depth study of biometric voter registration in Chad, a country marked by a long history of political violence, the article explains how the technology has been construed as a "solution" to address a situation labelled as a political crisis. To make sense of the unlikely introduction of biometrics in Chad, two main elements are considered: the socially constituted belief in the potential of biometrics and – paradoxically – the unfulfilled promises and fallibility of that same technology. Combining the literature on biometrics, election technologies, and liberal democracy promotion, the analysis concludes that biometric voter registration is a disciplining technology. In addition to capturing the personal data of individuals, it fosters the framing of democracy in narrow technological and procedural terms.